When influential directors meet tax havens: Evidence on conforming tax avoidance - Burhan, Annisa Hayatun Nazmi (Journal of Accounting and Investment, 2026)
Research aims: This study aims to investigate the correlation of influential director, the interactions with tax havens, and the tendency of firms to engage conforming tax avoidance. Design/Methodology/Approach: This study employs a quantitative method using secondary data, of Indonesian firms. With panel data from the years 2010-2022, this study performs purposive sampling and moderating regression analysis to test the hypotheses. The technique also involves Social Network Analysis (SNA) with Gephin 10 to generate the influential director measurement, and regression analysis using STATA. Research findings: The study found that firms having influential director associates with conforming tax avoidance. The findings further show that interactions of influential directors with tax havens show a higher tendency to avoid tax.Theoretical contribution/ Originality: This study contributes to the literature of social network and taxation by presenting on the role of director networks in tax information spillover, that is amplified by the presence of tax haven affiliates. Practitioner/Policy implication: Network-based perspective enables regulators to identify the most central taxpayers (i.e., multinational corporations) that have high influence on information spillover. With the evidenciary support of tax havens, a tax authority may then be inspired to tighten anti-avoidance regulations targeting firms that utilize tax haven affiliations. Research limitation/Implication: This study focus only on the Social Network Theory concept of centrality and limits the SNA to identify the most influential directors by using proxy of eigenvector centrality. Future research is recommended to extend the analysis to other centrality values and other types of networks for more comprehensive findings.